Palm oil and cardiovascular disease: a randomized trial of the effects of hybrid palm oil supplementation on human plasma lipid patterns. Issue 1 (21st October 2015) - Lucci, P.; Borrero, M.; Ruiz, A.; Pacetti, D.; Frega, N. G.; Diez, O.; Ojeda, M.; Gagliardi, R.; Parra, L.; Angel, M.
Abstract : Hybrid palm oil supplementation (25 mL per day – 3 months) positively influences cardiovascular risk-factor profiles by significantly decreasing TC and LDL-C levels. Abstract : This study examines, for the first time, the effect of hybrid Elaeis oleifera × E. guineensis palm oil supplementation on human plasma lipids related to CVD risk factors. One hundred sixty eligible participants were randomized and assigned to one of the two treatments: 25 mL hybrid palm oil (HPO group) or 25 mL extra virgin olive oil (EVOO group) daily for 3 months. Fasting venous samples were obtained at baseline and after 1, 2 and 3 months for measurement of plasma lipids (TC, LDL-C, HDL-C and TAGs). Changes in body mass index and waist circumference were also assessed. Although there was an overall reduction in TC (7.4%, p < 0.001) and in LDL-C (15.6%, p < 0.001), no significant differences were found between the treatment groups in a repeated measures analysis of variance for TC ( p = 0.0525), LDL-C ( p = 0.2356), HDL-C ( p = 0.8293) or TAGs ( p = 0.3749). Furthermore, HPO consumption had similar effects on plasma lipids to EVOO, thus providing additional support for the concept that hybrid Elaeis oleifera × E. guineensis palm oil can be seen as a "tropical equivalent of olive oil".